Case studies on illegal production of ephedrine/pseudoephedrine within Fujian China. (July 2020) - Zhu, Binling; Conlan, Xavier; Cao, Jie; Meng, Liang; Zheng, Kefang; Yang, Duoping; Yang, Wenrong
Graphical abstract: There were three main ways of illicit production Ephedrine/pseudoephedrine (EPH) observed. The raw materials were ephedra herb (a), Contac tablets (b) and 2-bromopropiophenone. Highlights: Ephedrine/Pseudoephedrine (EPH) is controlled within China. A summary of the 50 cases of illegal production of EPH is presented. There were three main ways of illicit production EPH observed. The manufacture of EPH via 2-bromopropiophenone was observed after 2013. Methcathinone as intermediate was detected in the samples. Abstract: Ephedrine/pseudoephedrine (EPH) is the most common precursor for the manufacture of methamphetamine and is controlled within China via criminal law and government regulations. Therefore, it is of great significance to systematically study the cases of illicit production of EPH in order to aid timely investigation into the production of precursor drugs. According to the literature, there are no comprehensive case studies on the illicit production of EPH. To address this, 50 cases involving the illicit production of EPH from Fujian Province in China were comprehensively explored and the quantitative data of the 762 collected samples were directly compared. In terms of the timeframe these cases occurred in, the results show that the number of such cases in Fujian Province increased significantly from 2012 to 2013 (10 cases -15 cases), but the number of cases decreased rapidly in 2016 (4 cases). Across the region of interest, the illegal production of EPH was mainly observed in Longyan, accounting for 32 cases (64.0 % of the total cases). Forty-two cases (84.0 % of the total cases) were located in remote mountains, abandoned pig farms, chicken farms and factories. In terms of the synthetic methodology used, initially (up until 2013) only the extraction of EPH from the ephedra plant and from commercially available tablets was observed. The manufacture of EPH via a direct chemical synthesis was only observed in this region after 2013 at which point a significant drop in the extraction methodologies was identified. The quality of the samples and the appearance of semi-finished products was shown to vary significantly across the cases with sample color ranging from light yellow, brown, tan for both seized solids and liquids. This data set gives some insights into the local issues specifically around EPH production in Chinese provinces and goes some way to help inform policing strategies.